LELUHUR DALAM KONTEKS ALIANSI PERKAWINAN MASYARAKAT KEI DI MALUKU - Ngutra, Seno; Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2019)
For society of Kei, the most important relationship is the relationship by marriage; every marriage unites two houses (groups) in a relationship called yan’ur-mang’ohoi. The yan’ur house is the groom‟s, while the mang’ohoi house is the bride‟s. Each house is thus related to a number of other houses, some of which are its mang’ohoi and others its yan’ur. In the accepted vocabulary of social anthropology, these of a marriage alliance relationship are defined as “wife-giver” and “wife-taker”. In this study, we focuses on mang’ohoi house in two issues: mang’ohoi house as origin of yan’ur house and mang’ohoi house in relation with the dead or mang’ohoi as most ancestors. This paper is based on data collected during fieldwork visits to different parts of Kei Islands, in the Southeast Moluccas. For good explication, this paper involves two steps. First, we question marriage alliance theory in general, in order to delimit its scope and to reconsider its appropriateness in the case of Kei society. Second, we attempt to trace more closely to society‟s concepts regarding the marriage system and its relation to values.